Aspects and Consequences of Employee Retention in Human Resource Practices: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human resource practices incorporate choosing human resource needs, screening, selecting, training, rewarding, evaluating just as taking care of work relations, safety and health, and decency concerns. Four elements of HRM practices analyzed in this investigation are training and development, career development, compensation and benefits, and performance appraisal. In the present investigation a few HRM practices (performance appraisal, special chances and job security) have been proposed to clarify its impact on employee's retention. Beforehand, different examinations have tried to consider the impact of HRM practices and employee’s retention however their outcomes are for the most part clashing, in this way further examination is required. The main aim of this paper is to define the aspects and consequences of performance of Employee Retention in HRM practices the outcomes demonstrated that distinctive human resource practices significantly affect the employee retention. This study also describe the outlook of the Global and Indian companies on employee retention management. Further the outcome uncovered that devotion intervenes the relation of HRM and organization of HRM and the aspects of HRM with Employee Retention.